Impact assessment of mobile agri support services on farmers’ aspirations in aspirational districts of India: A difference-in-differences approach - Shireesha, D; Jagan, M R M; Prasad, P (Plant Science Today, 2026)
The present study assesses the impact of Mobile Agri Support Services (MASS), a digital–physical agricultural extension initiative conceptualised and implemented by the Extension Education Institute (EEI), Professor Jayashankar Telangana Agricultural University (PJTAU), in collaboration with Evergreen Energy Enterprises Pvt. Ltd., on farmers’ aspirations in three selected aspirational districts of Telangana. The MASS is a unique 'phygital' (physical + digital) platform tested for a period of one year (2nd June 2023 to 31st July, 2024) aimed at addressing critical gaps in agricultural extension by delivering real-time, hyperlocal and technology-enabled agricultural services. The study adopts an experimental research design involving 600 beneficiary farmers (experimental group) and 400 non-beneficiary farmers (control group) across 6 villages from each mandal. Employing the difference-in-difference (DID) technique, the study measures pre- and post-intervention changes in technological, economic, environmental and social aspirations of farmers. Data collection was conducted through structured interviews and analysed using statistical tools like frequency, percentage, arithmetic mean and Z-tests. A DID approach was employed to estimate the causal effect of the intervention on technological, economic, environmental and social aspirations. The results indicate a substantial positive shift in the aspirations of beneficiary farmers following the intervention. In the sample area, aspirations towards technological change increased from 19.52 to 48.41 units, reflecting a significant gain of 28.89 units, while no change was observed in the non-sample area (14.54 units before and after). Similarly, economic aspirations rose from 5.73 to 16.96 units in the sample area, showing an improvement of 9.85 units compared to a marginal increase in the non-sample area (5.53 to 6.64 units). Aspirations related to environmental change exhibited a marked rise from 15.65 to 94.45 units, indicating a substantial enhancement of 70.93 units relative to the non-sample area (8.20 to 16.16 units). Additionally, another dimension showed an increase from 11.65 to 35.20 units in the sample area, with a corresponding gain of 21.55 units, compared to only a slight change in the non-sample area (11.43 to 13.43 units). In contrast, non-beneficiary farmers in control areas exhibited static or marginal changes. Thus the MASS initiative demonstrated its potential in enhancing farmers' aspirations and capacities towards sustainable agricultural development, especially in backward regions, suggesting its scalability and relevance in similar agrarian contexts. The findings indicate significant post-intervention improvements among beneficiary farmers across all aspiration dimensions, while no meaningful changes were observed in control areas.